Brachytydeus Thor - Silva, Guilherme Liberato Da; Metzelthin, Maicon Henrique; Silva, Onilda Santos Da; Ferla, Noeli Juarez (Zenodo, 2016)
Brachytydeus Thor Brachytydeus Thor, 1931; Raphitydeus Thor, 1933: 54 sensu André, 2005; Lorryia (Oudemans, 1925) sensu (Kaźmierski, 1989 b); Ueckermann & Grout, 2007: 2361; Kaźmierski, 2008 a: 357 –363, 2008b: 79–85, 2009 a: 107– 117, 2009 b: 347–355; Silva et al. 2013: 620, 2014a: 498-500, 2016: 1–8; Venil ia Kuznetzov, 1979: 592–599; Kuznetsovia 2006: Kammerer, 2006: 269. Type species : Tydeus cruciatus Koch sensu André (2005). 25. Brachytydeus aberrans (Oudemans, 1932): 350, Norway, from moss. Other names: Tydeus aberrans— original, Lorryia aberrans— Kaźmierski (1998). Type depository: National Museum of Natural History, Leiden, The Netherlands. 26. Brachytydeus adamantiae (Panou & Emmanouel, 1995 d): 177, Greece, from moss. Other names: Lorryia adamantiae— original, Lorryia adamantiae— Kaźmierski (1998). Type depository: Acari Collection, Laboratory of Agricultural Zoology & Entomology, Agricultural University of Athens, Greece. 27. Brachytydeus aegyptiaca (Rasmy & El-Bagoury, 1979): 195, Egypt, soil sample of а mango orchard. Other names: Paralorryia aegyptiaca— original, Lorryia aegyptiaca— Kaźmierski (1998). Type depository: Acarina collection of Cairo University, Egypt. 28. Brachytydeus akelai (Kaźmierski, 1998): 309, India, from pieces of wood and goat excrement next to moist scrubs of Salix sp. Other names: Lorryia akelai— original. Type depository: Zoological Museum in Hamburg, Germany. 29. Brachytydeus alykaenae (Panou & Emmanouel, 1996): 98, Greece, from unidentified alpine plant. Other names: Lorryia alykaenae— original, Lorryia alykaenae— Kaźmierski (1998). Type depository: Acari Collection, Laboratory of Agricultural Zoology & Entomology, Agricultural University of Athens, Greece. 30. Brachytydeus amica (Kaźmierski, 1998): 312, Hungary and Turkey, from young deciduous forest ( Quercus sp., Robinia sp., Lactuca muralis (L.), Galium sp., Astragalus glycyphyllos L., Veronica sp., Evonymus sp.) and Cotoneaster bullatus Boiss. Other names: Lorryia amica— original, Brachytydeus amica— Tempfli et al. (2015). Type depository: Department of Animal Morphology, Adam Mickiewicz University, Poland. 31. Brachytydeus ancora (Karg, 1973): 222, Germany, from forest soils between the grass roots and moss. Other names: Lorryia ancora— original. Lorryia ancora— Kaźmierski (1998). Type depository: Instituts für Pflanzenschutzforschung, Berlin, Germany. 32. Brachytydeus ancoraria (Karg, 1975): 103, Germany, from apple leaves. Other names: Tydeus ancorarius— original, Lorryia ancoraria— Kaźmierski (1998), Donczyk (2006). Type depository: Instituts für Pflanzenschutzforschung, Berlin, Germany. 33. Brachytydeus argentinensis (Baker, 1968 b): 1099, Argentina, from under calyx of lime. Other names: Paralorryia argentinensis— original, junior homonym of Tydeus argentinensis Baker (1970), Lorryia argentinensis— Kaźmierski (1998). Type depository: National Museum of Natural History (NMNH), Washington, D.C., USA. 34. Brachytydeus arkadiensis (Panou & Emmanouel, 1995 b): 217, Greece, from moss. Other names: Lorryia arkadiensis— original, Lorryia arkadiensis— Kaźmierski (1998). Type depository: Acari Collection, Laboratory of Agricultural Zoology & Entomology, Agricultural University of Athens, Greece. 35. Brachytydeus armindae (Momen & Lundqvist, 2005): 229, Sweden, from lichens in mosses. Other names: Tydeus armindae— original. Type depository: Museum of Zoology, Lund University, Sweden. 36. Brachytydeus artichokei (El-Bagoury & Momen, 1989): 122, Egypt, from Cynara scolymus L. Other names: Tydeus artichokei— original, Lorryia artichokei— Kaźmierski (1998). Type depository: Acarology Research Unit, National Research Centre, Dokki, Cairo, Egypt. 37. Brachytydeus atyeoi (Baker, 1968 a): 996, United States of America, from litter. Other names: Lorryia atyeoi— original, Lorryia atyeoi— Kaźmierski (1998), Ripka et al. (2005), Ripka et al. (2013 a). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 38. Brachytydeus australensis (Baker, 1970): 168, Australia, from celery leaves. Other names: Tydeus australensis— original, Lorryia australensis— Kaźmierski (1998). Type depository: National Museum of Natural History (NMNH), Washington, D.C., USA. 39. Brachytydeus baderi (Schiess, 1981): 96, Switzerland, from Caricetum firmae Rübel. Other names: Tydeus baderi— original, Lorryia baderi— Kaźmierski (1998), Brachytydeus baderi— Kaźmierski (2008 a). Type depository: Basel Museum. 40. Brachytydeus bakeri (Zaher & El-Bagoury, 1981): 179, Egypt, from palm trees. Other names: Paralorryia bakeri— original, Lorryia bakeri— Kaźmierski (1998), Brachytydeus bakeri— Kaźmierski (2008 b). Type depository: Faculty of Agriculture, Cairo University, Egypt. 41. Brachytydeus balcanica (Natchev & Simova, 1978): 71, Bulgaria, from leaves and twigs of Prunus domestica L. Other names: Tydeus balcanicus— original, Lorryia balcanica— Kaźmierski (1998), Brachytydeus balcanicus— Kaźmierski (2008 a). Type depository: Author’s collection. 42. Brachytydeus bathorii (Ripka & Kaźmierski in Ripka et al. 2013 a): 24, Hungary, from Tilia cordata Mill. Other names: Lorryia bathorii— original, Lorryia (cf.) elinguis sp. n. III — Ripka & Kaźmierski (1998 a). Type depository: Department of Animal Morphology, Adam Mickiewicz University, Poland. 43. Brachytydeus bedfordiensis (Evans, 1952): 664, Canada, from stored grain, litter under Fagus grandifolia Ehrh., moss, apple tree, grain spill. Other names: Lorryia bedfordiensis— original, Tydeus bedfordiensis— André (1987), Lorryia bedfordiensis— Baker (1968 a), Kaźmierski (1998). Type depository: British Museum (Natural History). 44. Brachytydeus belfiori (Momen & Lundqvist, 2005): 229, Sweden, from Sphagnum mosses and lichens on branches. Other names: Tydeus belfiori— original. Type depository: Museum of Zoology, Lund University, Sweden. 45. Brachytydeus benensis (Baker, 1968 a): 998, Congo Democratic Republic, from Tithonia speciosa Goldfinger. Other names: Lorryia benensis— original, Lorryia benensis— Kaźmierski (1998), Brachytydeus benensis— Silva et al . (2016). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 46. Brachytydeus berryi (Baker, 1968 b): 1100, Mexico, from citrus leaves. Other names: Paralorryia berryi— original, Lorryia berryi— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 47. Brachytydeus blaszaki (Kaźmierski, 1998): 313, India, from pine-spruce-fur forest with addition of hazel, wild strawberry, clover and high grass. Other names: Lorryia blaszaki— original. Type depository: Zoological Museum in Hamburg, Germany. 48. Brachytydeus bloszyki (Kaźmierski, 1998): 314, India, from fallen leaves, detritus and scrubs of Papilionaceae. Other names: Lorryia bloszyki— original. Type depository: Zoological Museum in Hamburg, Germany. 49. Brachytydeus brachypous (Panou & Emmanouel, 1995 c): 212, Greece, from Astragalus sp. Other names: Lorryia brachyopus— original. Type depository: Acari Collection, Laboratory of Agricultural Zoology & Entomology, Agricultural University of Athens, Greece. 50. Brachytydeus brevicula (Koch, 1838): No page, Germany and Italy, old pine forest mixed with young oaks, dry detritus from old oak and moss from Robinia sp. Other names: Tydeus breviculus— original, Tydeus breviculus— Koch (1842), Brachtydeus breviculus— Thor (1931; 1933), Lorryia brevicula— Kaźmierski (1997 b), Kaźmierski (1998), Donczyk (2006), Tydeus curtus - Berlese (1910 a), Thor (1933), Bernini, Castagnoli & Nannelli (1995). Redescription: Kaźmierski (1998): 305. Type depository: Holotype lost. 51. Brachytydeus brusti (Momen & Sinha, 1991): 1245, Canada, from stored grain. Other names: Tydeus brusti— original, Lorryia brusti— Kaźmierski (1998). Type depository: Canadian National Collection at the Biosystematics Research Centre, Agriculture Canada, Ottawa, Ontario, Canada. 52. Brachytydeus caputoperio (Momen & Lundqvist, 1995): 46, Sweden, grasses, lichens on the ground. Other names: Tydeus caputoperio— original, Lorryia caputoperio— Kaźmierski (1998). Type depository: Zoological Museum, Lund University, Sweden. 53. Brachytydeus carya (Baker, 1968 b): 1105, United States of America, from bark of Carya sp. Other names: Paralorryia carya— original, Paralorryia carya— Momen & Lundqvist (1996 b), Lorryia carya— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 54. Brachytydeus catenulata (Thor, 1931): 91, Norway; from moss and lichens. Other names: Retetydeus catenulata— original, Tydeus catenulata— Momen & Lundqvist (1995), Lorryia catenulata— Baker, (1968 a), Kaźmierski (1998), Donczyk (2006). Type depository: Unknown. 55. Brachytydeus caudata (Kuznetzov, 1979): 1413, Crimea, from forest litter. Other names: Venilia caudata (Kuznetzov, 1979) — original, Lorryia caudata— Kaźmierski (1998), Kuznetsovia caudata— Kammerer (2006). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 56. Brachytydeus celtides (Ueckermann & Smith Meyer, 1979 a): 122, South Africa, from Celtis africana N.L.Burm. Other names: Paralorryia celtides— original, Lorryia celtides— Kaźmierski (1998). Type depository: National Collection of Acari, Plant Protection Research Institute, Pretoria, South Africa. 57. Brachytydeus chapultepecensis (Baker, 1943): 185, Mexico, from lichens. Other names: Melanotydcus chapultepeccnsis— original, Paralorryia chapultepecensis (Baker 1968 b), Pseudolorryia chapultepecensis— Kaźmierski (1989 b), Lorryia chapultepecensis— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 58. Brachytydeus chiapensis (Baker, 1947): 135, Mexico, from leaf mold. Other names: Lorryia chiapensis— original, Lorryia chiapensis— Baker (1968). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 59. Brachytydeus collicupata (Schiess, 1981): 87, Switzerland, from Caricetum firmae Rübel. Other names: Tydeus collicupatus— original, Lorryia collicupata— Kaźmierski (1998) Type depository: Basel Museum. 60. Brachytydeus collyerae (Baker, 1968 a): 994, New Zealand, from Rubus sp. Other names: Lorryia collyerae— original, Lorryia collyerae— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 61. Brachytydeus comaliatus Kaźmierski, 2008 a: 350, Russia, from litter and soil. Type depository: Department of Animal Morphology collection, Adam Mickiewicz University, Poland. 62. Brachytydeus concinna (Oudemans, 1929 b): 427, The Netherlands, from farm house. Other names: Tydeus concinnus— original, Paralorryia concinna— Baker (1968 b), Lorryia concinna— Oudemans (1929 b), Thor (1933). Redescription: Kaźmierski (1998): 319. Type depository: National Museum of Natural History, Leiden, The Netherlands. 63. Brachytydeus cooremani (Baker, 1968 a): 1001, United States of America, from coconut leaves. Other names: Lorryia cooremani— original, Lorryia cooremani— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 64. Brachytydeus crassidigitosus Kaźmierski, 2009 b: 111, Poland, from moss, decaying grass, detritus and soil from insolated calcareous crevices and rocks. Type depository: Department of Animal Morphology collection, Adam Mickiewicz University, Poland. 65. Brachytydeus cruciatus (Koch, 1838): No page, Germany, unknown. Other names: Tydeus cruciatus— original, Lorryia cruciatus— Kaźmierski (1998). Type depository: Unknown. 66. Brachytydeus crucifera (Karg, 1973): 225, Hiddensee Island (Germany), from dead roots in wet soil. Other names: Lorryia crucifera— original, Lorryia crucifera— Kaźmierski (1998). Type depository: Instituts für Pflanzenschutzforschung, Berlin, Germany. 67. Brachytydeus danhidalgoi (Kaźmierski, 1998): 302, Slovakia, from mixed forest with birches, pines and aspens. From soils, grass, moss and ferns. Other names: Lorryia danhidalgoi— original. Type depository: Zoological Museum in Hamburg, Germany. 68. Brachytydeus danielssoni (Momen & Lundqvist, 1995): 49, Sweden, from grasses and bark of dead pine tree. Other names: Tydeus danielssoni— original, Lorryia danielssoni— Kaźmierski (1998). Type depository: Zoological Museum, Lund University, Sweden. 69. Brachytydeus danutae (Kaźmierski, 1978 a): 473, Poland, from debris of old strawrick and soil samples in mixed forest on the dry ground. Other names: Lorryia danutae— original, Tydeus danuta— Momen & Lundqvist (1995), Lorryia danutae— Kaźmierski (1990, 1998), Donczyk (2006). Type depository: Department of Animal Morphology collection, Adam Mickiewicz University, Poland. 70. Brachytydeus devexa (Kuznetzov, in Kuznetzov & Livshitz 1973 b): 17, Crimea, from forest litter. Other names: Tydeus devexus— original, Lorryia devexa— Kaźmierski (1998), Donczyk (2006). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 71. Brachytydeus dorothyae (Momen, 1994): 133, Ireland, from the bark of apple trees Other names: Tydeus dorothyae— original, Lorryia dorothyae— Kaźmierski (1998). Type depository: National Museum of Ireland. 72. Brachytydeus draciformis (Kaźmierski, 1998): 294, Spain, from moss at the base of trunk of Quercus pyrenaica Willd. Other names: Lorryia draciformis— original, Brachytydeus draciformis— Kaźmierski (2008 b). Type depository: Zoological Museum in Hamburg, Germany. 73. Brachytydeus dumosa (Kuznetzov, in Kuznetzov & Livshitz 1973 b): 14, Crimea, from elm. Other names: Tydulosus dumosus— original, Lorryia dumosa— Kaźmierski (1998). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 74. Brachytydeus echinulata (Kuznetzov, 1971): 1740, Georgia, from moss. Other names: Lorryia echinulata— original, Lorryia echinulata— Kaźmierski (1998). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 75. Brachytydeus eharai (Baker, 1968 b): 1104, Japan, from Cycas revoluta Thunb. Other names: Paralorryia eharai— original, Lorryia eharai— Kaźmierski (1998). Type depository: United States National Museum of Natural History (USNM) at Beltsville, Maryland, USA. 76. Brachytydeus electra (Kuznetzov, 1973 a): 773, Crimea, from bark of Ulmus sp. Other names: Lorryia electra— original, Lorryia electra— Kaźmierski (1998). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 77. Brachytydeus elegans (Kaźmierski, 1998): 318, Poland, from stable, sweepings from behind feeding trough. Other names: Lorryia elegans— original. Type depository: Zoological Museum in Hamburg, Germany. 78. Brachytydeus elinguis (Kuznetzov, in Kuznetzov & Livshitz, 1973): 51, Crimea, from Cornus mas L. Other names: Tydeus elinguis— original, Lorryia elinguis— Kaźmierski (1998). Type depository: Department of Entomology and Phytopathology of the State Nikitsky Botanical Garden, Yalta, Crimea. 79. Brachytydeus epimekes (Panou & Kaźmierski, 1996): 7, Greece, from unidentified plant. Other names: Lorryia epimekes : Published as part of Silva, Guilherme Liberato Da, Metzelthin, Maicon Henrique, Silva, Onilda Santos Da & Ferla, Noeli Juarez, 2016, Catalogue of the mite family Tydeidae (Acari: Prostigmata) with the world key to the species, pp. 1-68 in Zootaxa 4135 (1) on pages 9-28, DOI: 10.11646/zootaxa.4135.1.1, http://zenodo.org/record/255684 : {"references": ["Thor, S. (1931) Norwegische Tydeidae I - VII, mit Kennzeichnung vier neuer gattungen. Zoologischer Anzeiger, 94 (3 / 4), 89 - 104. http: // dx. doi. org / 10.1080 / 01647954.2011.619576", "Thor, S. (1933) Acarina, Tydeidae, Ereynetidae. Tierreich, Walter de Gruyter, 60, 1 - 82.", "Andre, H. M. (2005) In search of the true Tydeus (Acari, Tydeidae). Journal of Natural History, 39, 975 - 1001. http: // dx. doi. org / 10.1080 / 00222930400002838", "Oudemans, A. C. (1925) Acarologische Aanteekeningen LXXIX. Entomologische Berichten, 7, 26 - 34.", "Kazmierski, A. (1989 b) Morphological studies on Tydeidae (Actinedida, Acari) I. Remarks about the segmentation, chaetotaxy and poroidotaxy of idiosoma. Acta zoologica cracoviensia, 32, 69 - 83.", "Ueckermann, E. A. & Grout, T. G. (2007) Tydeoid mites (Acari: Tydeidae, Edbakerellidae, Iolinidae) occurring on Citrus in southern Africa. Journal of Natural History, 41, 2351 - 2378. http: // dx. doi. org / 10.1080 / 00222930701589921", "Kazmierski, A. (2008 a) Three new tydeid species of the genus Brachytydeus Thor, 1931 sensu Andre 2005 (Acari: Actinedida: Tydeidae) from Siberia. Annales Zoologici, 58, 347 - 355.", "Silva, G. L., Rocha, M. S., Reichert, M. B. & Ferla N. J. (2013) A new species of the genus Brachytydeus Thor, 1931 sensu Andre, 2005 (Acari: Tydeidae) from Rio Grande do Sul State, Brazil, with a key to the species in the Americas. International Journal of Acarology, 39, 620 - 624. http: // dx. doi. org / 10.1080 / 01647954.2013.861510", "Kammerer, C. F. (2006) Notes on some preoccupied names in Arthropoda. Acta Zootaxonomica Sinica, 31, 269 - 271.", "Oudemans, A. C. (1932) Acarologische Aanteekeningen CXII. Entomologische Berichten, 8, 350 - 352.", "Panou, H. N. & Emmanouel, N. G. (1995 d) Lorryia adamantiae, a new species of tydeid mite from Greece (Acari: Prostigmata).", "Rasmy, A. H. & El-Bagoury, M. E. (1979) A new species of genus Paralorryia from Egypt (Acarina: Tydeidae). Acarologia, 21, 194 - 196.", "Panou, H. N. & Emmanouel, N. G. (1996) Two new species of Lorryia (Acari: Tydeidae) from Greece. Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 12, 91 - 103.", "Tempfli, B., Penzes, B., Fail, J. & Szabo, A. (2015) The occurrence of tydeoid mites (Acari: Tydeoidea) in Hungarian vineyards. Systematic & Applied Acarology, 20, 937 - 954. http: // dx. doi. org / 10.11158 / saa. 20.8.9", "Karg, W. (1973) Drei neue Tydeidenarten der Gattung Lorryia Oudemans, 1925 (Acarina, Trombidiformes). Zoologischer Anzeiger, 191, 218 - 229.", "Karg, W. (1975) Zur Kenntnis der Tydeiden (Acarina, Trombidiformes) aus Apfelanlagen. Zoologischer Anzeiger, 194, 91 - 110.", "Donczyk, J. (2006) Free-living Tydeoidea (Acari: Actinedida) from the vicinity of Gniew (northern Poland): preliminary report. Biological Letters, 43, 163 - 168.", "Baker, E. W. (1968 b) The genus Paralorryia. Annals of the Entomological Society of America, 61, 1097 - 1106. http: // dx. doi. org / 10.1093 / aesa / 61.5.1097", "Panou H. N. & Emmanouel, N. G. (1995 b) Lorryia arkadiensis, a new species of tydeid mite from Greece (Acari: Prostigmata). International Journal of Acarology, 21, 217 - 221. http: // dx. doi. org / 10.1080 / 01647959508684061", "Momen, F. M. & Lundqvist, L. (2005) The genera Metalorryia and Tydeus (Acari: Prostigmata: Tydeidae), new and unrecorded species from south Sweden, International Journal of Acarology, 31, 225 - 236. http: // dx. doi. org / 10.1080 / 01647950508684425", "Baker, E. W. (1968 a) The genus Lorryia. Annals of the Entomological Society of America, 61, 986 - 1008. http: // dx. doi. org / 10.1093 / aesa / 61.4.986", "Ripka, G., Fain, A., Kazmierski, A., Kreiter, S. & Magowski, W. L. (2005) New data to the knowledge of the mite fauna of Hungary (Acari: Mesostigmata, Prostigmata and Astigmata). Acta Phytopathologica et Entomologica Hungarica, 40, 159 - 176. http: // dx. doi. org / 10.1556 / APhyt. 40.2005.1 - 2.13", "Ripka, G., Laniecka, I. & Kazmierski, A. (2013 a) On the arboreal acarofauna of Hungary: Some new and rare species of prostigmatic mites (Acari: Prostigmata: Tydeidae, Iolinidae and Stigmaeidae). Zootaxa, 3702 (1), 1 - 50. http: // dx. doi. org / 10.11646 / zootaxa. 3702.1.1", "Schiess, T. (1981) Neue Tydeidenarten (Acari, Actinedida, Tydeidae) aus einem alpinen Rasen (Caricetum firmae, 2500 m) des Schweizer Nationalparkes. Entomologica Basiliensia, 6, 78 - 107.", "Zaher, M. A. & El-Bagoury, M. E. (1981) A new mite, Paralorryia bakeri n. sp. from Egypt (Prostigmata: Tydeidae). Acarologia, 22, 179 - 180.", "Kazmierski, A. (2008 b) Description of two new species of Tydeinae (Acari: Actinedida: Tydeidae) from Spain with the remarks about the Iberian species of subfamily. Annales Zoologici, 58, 357 - 363.", "Natchev, P. & Simova, S. (1978) A new species mite of the family Tydeidae (Acarina). Acta Zoologica Bulgarica, 10, 71 - 74.", "Ripka, G. & Kazmierski, A. (1998) New data to the knowledge on the tydeid fauna in Hungary (Acari: Prostigmata). Acta Phytopathologica et Entomologica Hungarica, 33, 407 - 418.", "Evans, G. O. (1952) Terrestrial Acari new to Britain. II. Annals and Magazines of Natural History, 12, 660 - 675. http: // dx. doi. org / 10.1080 / 00222935208654337", "Andre, H. M. (1987) Tydeinae (Acari: Tydeidae) from Belgium. II. The genera Tydeus, Idiolorryia and Metalorryia. Acarologia, 28, 151 - 159.", "Silva, G. L., Radaelli, T. F. S., Metzelthin, M. H., Ferla, J. J. & Ferla, N. J. (2016) Two new species of Tydeidae (Acari: Prostigmata) records of species of this family and Triophtydeidae from Brazil. Zoologia, 33, e 20150130. http: // dx. doi. org / 10.1590 / S 1984 - 4689 zool- 20150130", "Panou, H. N. & Emmanouel, N. G. (1995 c) New records of tydeid mites from Greece with description of Lorryia brachypous sp. nov. (Acari: Tydeidae). Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 11, 211 - 220.", "Koch, C. L. (1838) Deutsche Crustacea, Myriopoda, Arachnida, 20 (11).", "Koch, C. L. (1842) Uebersicht des Arachnidensystems, 3, 1 - 130.", "Kazmierski, A. (1997 b) Penthaleidae, Tydeidae and Ereynetidae. pp. 209 - 211. In: Razowski, J., (Ed.), Checklist of Animals of Poland, Polish Academy of Science, Institute of Systematics and Evolution of Animals, Cracow, 4 (1 - 31), 260 pp. [In Polish, with English translation]", "Berlese, A. (1910 a) Acari nuovi. Manipulus V. Redia, 6, 199 - 234.", "Bernini, F., Castagnoli, M. & Nannelli, R. (1995) Arachnida - Acari. In: Minelli, A., Ruffo, S. & La Posta, S. (Eds.), Checklist delle specie della fauna italiana, 24, pp. 37 - 38.", "Momen, F. M. & Sinha, R. N. (1991) Tydeid mites associated with store grain and oilseeds in Canada, with descriptions of a new genus and five new species (Acari: Tydeidae). Canadian Journal of Zoology, 69, 1226 - 1253. http: // dx. doi. org / 10.1139 / z 91 - 175", "Momen, F. M. & Lundqvist, L. (1995) The genus Tydeus (Acari: Prostigmata) in Southern Sweden, six new species. Acarologia, 36, 41 - 53.", "Momen, F. M. & Lundqvist, L. (1996 b) Corticolous mites; new and unrecorded species of the genus Tydeus (Acari: Prostigmata: Tydeidae) and a key to species of Southern Sweden. Acarologia, 37, 83 - 96.", "Baker, E. W. (1943) Nuevos Tydeidae Mexicanos (Acarina). Revista de la Sociedad Mexicana de Historia Natural, 4, 181 - 189.", "Baker, E. W. (1947) Notes on the mites of the family Tydeidae (Acarina) with descriptions of two new species. Proceedings of the Entomological Society of Washington, 49, 133 - 136.", "Oudemans, A. C. (1929 b) Acarologische Aanteekeningen XCVI. Entomologische Berichten, 7, 421 - 429.", "Kazmierski, A. (2009 b) Three new Tydeinae species (Acari: Actinedida: Tydeidae) from Poland. Annales Zoologici, 59, 107 - 117.", "Kazmierski, A. (1978 a) Lorryia danutae sp. nov. (Acari, Prostigmata); a new species of tydeid mite from Poland. Bulletin of the Polish Academy of Science, 26, 473 - 478.", "Kuznetzov, N. N. (1971) Seven species of the genus Lorryia (Tydeidae) from Crimea and Georgia. Zoologicheskii Zhurnal, 50, 1740 - 1746. [In Russian]", "Panou H. N. & Kazmierski, A. (1996) Lorryia epimekes, a new species of tydeid mite from Greece (Acari: Prostigmata). Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 12, 7 - 14.", "El-Bagoury, M. E. & Momen, F. M. (1988) Description of two new tydeid mites from Egypt (Acari, Tydeidae). Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 9, 109 - 113.", "Baker, E. W. (1944 a) Seis especies de Lorryia (Acarina: Tydeidae). Annales de Instituto de Biologia de Mexico, 15, 215 - 222.", "El-Bagoury, M. E. (1978) Ecological and biological studies on mites of the family Tydeidae. Ph. D. Thesis, Cairo University.", "Garcia Mari, F., Laborda, R., Costa Comelles, J., Ferragut, F. & Marzal, C. (1985) Acaros fitofagos y depredatores de nuestros citricos. Cuadernos de Fitopatologia, 2, 54 - 63. [In Spanish]", "Garcia Mari, F., Ferragut, F., Marzal, C., Costa Comelles, J. & Laborda, R. (1986) Acaros que viven en la hojas de los citricos espanoles. Investigacion Agraria Produccion y Proteccion Vegetales, 1, 219 - 250. [In Spanish]", "Castagnoli, M. (1984) Contributo alla conoscenza dei Tideidi (Acarina: Tydeidae) delle piante coltivate in Italia. Redia, 67, 307 - 322.", "Kamali, K., Ostovan, H. & Atamehr, A. (2001) A Catalog of the Mites and ticks (Acari) of Iran. Islamic Azad Scientific Publication centre, 192 pp.", "Sadeghi, H., Laniecka, I. & Kazmierski, A. (2012) Tydeoid mites (Acari: Triophtydeidae, Iolinidae, Tydeidae) of Razavi Khorasan Province, Iran, with description of three new species. Annales Zoologici, 62, 99 - 114. http: // dx. doi. org / 10.3161 / 000345412 X 633685", "Kuznetzov, N. N. (1975 a) New species of the genus Lorryia (Acariformes: Tydeidae). Zoologicheskii Zhurnal, 54, 127 - 130.", "Kazmierski, A. (2009 a) Brachytydeus szeptyckii sp. n. (Acari: Actinedida: Tydeidae); a new tydein mite from Poland. Acta zoologica cracoviensia, 52, 79 - 85.", "Cooreman, J. (1958) Notes et observations sur les acariens. VII. Photia gracca n. sp. (Acaridiae, Canestriniidae) et Lorryia formosa n. sp. (Stomatostigmata, Tydeidae). Bulletin de l'Institut Royal des Sciences Naturelles de Belgique Entomologie, 34, 1 - 10.", "Faraji, F. & Kamali, K. (1993) Mites associated with Citrus spp. in eastern Mazandaran. Proceedings of the 11 th Iranian Plant Protection Congress, Rasht, 186 pp.", "Sousa, J. M., Gondim Jr., M. G. C., Lofego, A. C. & Moraes, G. J. de. (2015) Mites on Annonaceae species in northeast Brazil and in the state of Para. Acarologia, 55, 5 - 18. http: // dx. doi. org / 10.1051 / acarologia / 20152147", "Silva, G. L., Cunha, U. S., Rocha, M. S., Panou, E. N. & Ferla, N. J. (2014 a) Tydeid and triophtydeid mites (Acari: Tydeoidea) associated with grapevine (Vitaceae: Vitis spp.) in Brazil, with the descriptions of species of Prelorryia (Andre, 1980) and Tydeus Koch, 1835. Zootaxa, 3814 (1), 495 - 511. http: // dx. doi. org / 10.11646 / zootaxa. 3814.4.3", "Johann, L., Klock, C. L., Ferla, N. J. & Botton, M. (2009) Acarofauna (Acari) associada a videira (Vitis vinifera L.) no Estado do Rio Grande do Sul. Biociencias, 17, 1 - 19.", "Eichelberger, C. R., Johann L., Majolo, F. & Ferla, N. J. (2011) Mites fluctuation population on peach tree (Prunus persica (L.) Batsch) and in associated plants. Revista Brasileira de Fruticultura, 33, 765 - 773. http: // dx. doi. org / 10.1590 / S 0100 - 29452011005000102", "Klock, C. L., Johann L., Botton, M. & Ferla, N. J. (2011) Mite fauna (Arachnida: Acari) associated to grapevine, Vitis vinifera L. (Vitaceae), in the municipalities of Bento Goncalves and Candiota, Rio Grande do Sul, Brazil. Checklist, 7, 522 - 536.", "Reichert, M., Silva, G. L., Rocha, M. S., Johann, L. & Ferla, N. J. (2014) Mite fauna (Acari) in soybean agroecosystem in the northwestern region of Rio Grande do Sul State, Brazil. Systematic & Applied Acarology, 19, 123 - 136. http: // dx. doi. org / 10.11158 / saa. 19.2.2", "Momen, F. M. & Lundqvist, L. (1996 a) A new genus, Quadrotydeus, and three new species of the family Tydeidae (Acari: Prostigmata) from Southern Sweden, International Journal of Acarology, 22, 3 - 10. http: // dx. doi. org / 10.1080 / 01647959608684074", "Kazmierski, A. (1991) Description of two new species of the genus Lorryia sensu Kazmierski (Acari: Actinedida. Tydeidae). Bulletin of the Polish Academy of Science, 39, 339 - 346.", "Canestrini, G. (1886) Prospetto dell'Acarofauna Italiana. Atti del Reale Instituto Veneto di Scienze, Lettere ed Arti, 6, 693 - 734.", "Kazmierski, A. & Panou, H. N. (1997) Lorryia reticuloinsignia, a new species of tydeid mite from the Balkan Peninsula (Acari: Prostigmata). Genus, 8, 727 - 734.", "Oudemans, A. C. (1928) Acarologische Aanteekeningen XCIV. Entomologische Berichten, 7, 374 - 382.", "Momen, F. M. & El-Bagoury, M. E. (1994) A new tydeid mite, Tydeus kattai sp. n. from Egypt (Acari, Tydeidae). Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 150, 127 - 131.", "Ueckermann, E. A. & Smith-Meyer, M. K. P. (1979 b) African Tydeidae (Acari). II. The genus Paralorryia Baker 1965. Phytophylactica, 11, 117 - 127.", "Kuznetzov, N. N. (1974) A contribution to the fauna of the family Tydeidae (Acariformes) of the Central Chernozem District. Zoologicheskii Zhurnal, 53, 1092 - 1093. [In Russian]", "Kazmierski, A. (1980) Description of Venilia longina sp. nov. (Acari, Actinedida: Tydeidae) with a key to all species of the genus. Bulletin of the Polish Academy of Science, 28, 647 - 652.", "Niedbala, W., Blaszak, C., Bloszyk, J., Kaliszewski, M. & Kazmierski, A. (1981) Mites (Acari). In: Biocenotic studies on soil fauna in Bialoleka Dworska. Fragmenta faunistica, 26, 105 - 156. [In Polish]", "Niedbala, W., Blaszak, C., Bloszyk, J., Kaliszewski, M. & Kazmierski, A. (1982) Soils mites (Acari) of Warsaw and Mazovia. Memorabalia zoologica, 36, 235 - 252.", "Niedbala, W., Bloszyk, J., Kaliszewski, M., Kazmierski, A. & Olszanowski, Z. (1990) Structure of soil mites (Acari) communities in urban Green Warsaw. Fragmenta faunistica, 33, 21 - 44. http: // dx. doi. org / 10.3161 / 00159301 FF 1990.33.3.021", "Barimani Varandi, H. & Kamali, K. (1998) Mites (Acari) associated with conifers in Mazandaran, northern province of Iran. Proceedings of the 13 th Iranian Plant Protection Congress, Karaj, 74 pp.", "Kuznetzov, N. N. & Livshitz, I. Z. (1973 c) Three new species of the genus Paralorryia (Acariformes, Tydeidae). Zoologicheskiy zhurnal, 52, 604 - 606.", "Hajiqanbar, M. R., Hadad Irani Nejad, K. & Talebi Chaichi, P. (2002) Mites associated with sugar beet foliage in Miandoab (East Azerbaijan). Proceedings of the 15 th Iranian Plant Protection Congress, Kermanshah, pp. 234 - 235.", "Oudemans, A. C. (1929 a) Acarologische Aanteekeningen XCV. Entomologische Berichten, 7, 393 - 399.", "Oudemans, A. C. (1929 c) Acarologische Aanteekeningen XCVIII. Entomologische Berichten, 7, 476 - 485.", "Panou, H. N. & Emmanouel, N. G. (1995 a) New records of tydeid mites from Greece with description of Lorryia mantiniensis sp. nov. (Acari: Tydeidae). International Journal of Acarology, 21, 17 - 21. http: // dx. doi. org / 10.1080 / 01647959508684038", "Marshall, V. G. (1970) Tydeid mites (Acari: Prostigmata) from Canada. 1. New and redescribed species of Lorryia. Annals of the Entomological Society of Quebec, 15, 17 - 52.", "Kuznetsov, N. N. & Livshitz, I. Z. (1973 d) New and little-known species of tydeid mites (Acariformes, Tydeidae) of the Crimean fauna. Biologicheskie nauki, 3, 13 - 18.", "Stojnic, B. (2001) Structural changes and functional relationships of phytoseiid complex (Acari: Phytoseiidae) in apple orchard. Belgrade, Ph. D. thesis. 224 pp. [in Serbian]", "Momen, F. M. & Lundqvist, L. (1996 c) Taxonomy of non- Tydeus genera of the mite family Tydeidae (Acari: Prostigmata) from moss, lichens and trees in Southern Sweden. Acarologia, 37, 281 - 297.", "Khanjani, M. & Ueckermann, E. A. (2003) Four new tydeid species from Iran (Acari: Prostigmata). Zootaxa, 182, 1 - 11.", "Gerson, U. (1968) Five tydeid mites from Israel (Acarina: Prostigmata). Israel Journal of Zoology, 17, 191 - 198.", "Karg, W. (1992 a) Drei neue Tydeidenarten aus dem mitteldeutschen Tiefland. Deutsche Entomologische Zeitschrift, 39, 421 - 426.", "Stojnic, B., Panou, H., Papadoulis, G., Petanovic, R. & Emmanouel, N. (2002) The present knowledge and new records of phytoseiid and tydeid mites Acari Phytoseiidae, Tydeidae for the fauna of Serbia and Montenegro. Acta Entomologica Serbica, 7, 111 - 117.", "Livshitz, I. Z., Kuznetzov, N. N. & Zapletina, V. P. (1972) New species of the family Tydeidae (Acariformes) from Crimea and Azerbaijan. Zoologicheskii Zhurnal, 51, 1578 - 1580.", "Bozai, J. (1997) Tydeidae fauna data from Hungary (Acari, Tydeidae). Novenyvedelem, 33, 77 - 79. [in Hungarian]", "Timar, E., Bozai, J. & Burges, G. (2004) Additions to the knowledge of mites living on garlic. Novenyvedelem, 40, 17 - 25. [in Hungarian]", "Kulikova, L. (2011) Mites of fruit plantations of the Republic of Moldova. Muzeul Olteniei Craiova. Oltenia, Studii si comunicari, Stiintele Naturii, 27, 55 - 62.", "Kazmierski, A. (1993) Two new Tydeinae mites (Acari: Actinedida: Tydeidae) from Kenya. Entomologische Mitteilungen aus dem Zoologischen Museum Hamburg, 11, 65 - 74.", "Ripka, G., Fain, A., Kazmierski, A., Kreiter, S. & Magowski, W. L. (2002) Recent data to the knowledge of the arboreal mite fauna in Hungary (Acari: Mesostigmata, Prostigmata, and Astigmata). Acarologia, 42, 271 - 281.", "Akbari, A., Haddad Irani-Nejad, K., Khanjani, M., Arzanlou, M. & Kazmierski, A. (2015 a) A new tydeid species (Acari: Tydeidae) with a key to Brachytydeus species from East Azerbaijan Province, Iran. Systematic and Applied Acarology, 20, 423 - 430. http: // dx. doi. org / 10.11158 / saa. 20.4.7", "Kulczycki, A. G. (1992) Peculiarities of plant dwelling tydeid mite distribution (Acariformes: Tydeidae) in Kanev Nature Reserve and its buffer zone. Vestnik Zoologii, 5, 50 - 56. [in Russian]", "Theron, N., Roets, F., Dreyer, L. L., Esler, K. J. & Ueckermann, E. A. (2012) A new genus and eight new species of Tydeoidea (Acari: Trombidiformes) from Protea species in South Africa. International Journal of Acarology, 38, 257 - 273.", "Andre, H. M. (1980) A generic revision of the family Tydeidae (Acari: Actinedida). IV. Generic descriptions, keys and conclusion. Annales de la Societe royale Zoologique de Belgie, 116, 103 - 168.", "Garman, P. 1948. Mite species from apple trees in Connecticut. Connecticut Agricultural Experiment Station Bulletin, 520, 1 - 27.", "Sinha, R. N. (1962) A note on associations of some mites with seedborne fungi from prairie provinces. Proceedings of the Entomological Society of Manitoba, 18, 51 - 53.", "Treat, A. E. (1975) Mites of moths and butterflies. Comstock Public Associates, Cornell University Press, Ithaca & London, pp. 362.", "Baker, E. W. (1965) A review of the genera of the family Tydeidae (Acarina), Advanced Acarology, 2, 95 - 131.", "Shiba, M. (1969) Free-living mites from Shiga Heights IBP Area II. Bulletin of the national Science Museum Tokyo, 12, 89 - 91.", "Moddares Awal, M. (1997) List of agricultural pests and their natural enemies in Iran. Ferdowsi University Press, Mashhad, No. 147, 364 pp.", "Ostovan, H. & Kamali, K. (1997) Biodiversity of mites (Acari) associated with elm bark beetle, Scolytus multistriatus (Marsh) (Col., Scolytidae) in parks of Tehran. Journal of Agriculture, Science and Research Branch of Azad University, Tehran, 3 (11 - 12): 23 - 67.", "Uusitalo, M. & Huhta, V. (1995) Soil Prostigmata (Acari) in a scots pine Forest in Southern Finland. In: The Acari. Physiological and ecological aspects of Acari-host relationships, Dabor, Warszawa, pp. 331 - 336.", "Womersley, H. (1937) Acarina. Australasian Antarctic Expedition 1911 - 1914. Scientific Reports Series C-Zoology and Botany, 10, 1 - 24.", "Andre, H. M. & Naudo, M. H. (1965) Pretydeus s